ОСОБЛИВОСТІ ТА АСОЦІАТИВНІСТЬ СПРИЙНЯТТЯ ГЕОМЕТРИЧНИХ ФОРМ (Педагогіка вищої та середньої школи, 2022)
Our article is dedicated to the matter how the man distinguish the shape, what he or she sees in it and what he or she feels instinctively, what associative images emerge in connection with the shape what individual peculiarities exist in perception of typical qualities and elements of shape and how they are connected with the aesthetic potential of the human being.